Structural changes caused by ultrasound pretreatment: Direct and indirect demonstration in potato cylinders - Miano A.C. (2019)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project n° 2016/18052-5; the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project n° 401004/2014-7 and the productivity grant of P.E.D. Augusto (306557/2017-7); Cienciactiva from the ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica“ (CONCYTEC, Peru) for the A.C. Miano (Contract 272-2015-FONDECYT) and M.L.Rojas (Contract 087-2016-FONDECYT) Ph.D. scholarships.